Knowledge, attitude and perception of health care providers and their patients regarding “Telemedicine” for otorhinolaryngeal care during the COVID-19 pandemic - Pradhan, Nishikanta; Panda, Nishant; Singh, Snigdha; Rout, Manas R.; Samantaray, Kabikanta (International Journal Of Community Medicine And Public Health, 2022)
Background: Telemedicine aids health care facilities in implementing response on otorhinolaryngeal care during the pandemic while also maintaining provision for essential health services. This study was taken up to highlight perception of doctors and patients and implementation benefit and drawbacks of telemedicine, despite the continuous effort to help reduce ailments of the patients via reduction in the in-person care during pandemic. Objectives were to assess knowledge, attitude and perception (KAP) among doctors and patients regarding telemedicine during COVID-19 pandemic. To determine the gaps and challenges experienced by the health care providers and the patients by telemedicine consultation. Methods: Cross sectional study conducted among the 18 doctors and house surgeons in department of otorhinolaryngology, KIMS Bhubaneswar and 486 patients who availed telemedicine for consultation from these health care professionals. A semi structured, mixed questionnaire was used. First phase of study was when patient contacted the doctor over phone, second was when doctor called up the patient for follow up and third was when both the doctors and patients were contacted to take their feedback on the study and assess their KAP on telemedicine. Data was analysed using SPSS-23 and Pearson’s correlation was used to determine any association. Results: 81%, 78.5% and 65.2% HCPs had good knowledge, attitude and perception score regarding telemedicine while among the patients the scores for good knowledge, attitude and perception were 42%, 21.4%, 15.4%, respectively. 88% HCPs and 84.8% patients were satisfied with e-health and were willing to continue this technology. Conclusions: The traditional clinic consultation has been modified during the pandemic to prevent and control transmission of the infection though it has both merits and demerits.